Effects of jicama (Pachyrhizus erosus L.) non-starch polysaccharides with different molecular weights on structural and physicochemical properties of jicama starch. (May 2023) - Huang, Jingjing; Yu, Manling; Wang, Shaoyun; Shi, Xiaodan
Abstract: Jicama, Pachyrhizus erosus L., is a kind of widely cultivated but underutilized crop across the world. It contains considerable amounts of starch and non-starch polysaccharides (NSPs), which have not been well studied. As the key characteristics for the processing, physicochemical and rheological properties of starch-based systems can be affected by the blending of NSPs. In the current study, jicama NSPs (named as PEP) were firstly fractionated to two sub-fractions (PEP-3P and PEP-6P) using gradient ethanol precipitation method. The three fractions showed differences in molecular weight ( M w ) and monosaccharide compositions. Then, the three jicama NSPs were introduced into the jicama starch (PES) system to explore their effects on PES. Results showed that jicama NSPs with larger M w promoted the leaching of amylose from PES, formed a denser and more uniform gel network structure. The pasting, thermal, and rheological tests indicated that the blending starch systems with jicama NSPs had lower viscosity, weaker thermal stability, and gel strength compared with the pure PES system. In addition, PEP-6P and PES blending systems had the strongest gel strength, which may be due to the narrower distribution of M w . In the in vitro system, the content of resistant starch of the complexes decreased after jicama NSPs were added. Analysis of the interaction force showed that the PES/PEP-6P complex had stronger hydrogen bonding and electrostatic interaction. These results provided new knowledge on underlying interaction mechanism between natural starch and NSPs. Graphical abstract: Image 1 Highlights: Jicama non-starch polysaccharide (PEP) were fractionated to PEP-3P and PEP-6P. Interactions between jicama starch (PES) and PEPs were explored. Polysaccharides with larger M w led to denser gel network but lower gel strength. Addition of PEPs lower the contents of resistant starch of PES. PEP-6P with higher M w and narrower distribution performs stronger interactions.